2015
DOI: 10.1016/j.rpor.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy delay in overall treatment time on local control and survival in head and neck cancer: Review of the literature

Abstract: Treatment delays in completing radiotherapy (RT) for many neoplasms are a major problem affecting treatment outcome, as increasingly shown in the literature. Overall treatment time (OTT) could be a critical predictor of local tumor control and/or survival. In an attempt to establish a protocol for managing delays during RT, especially for heavily overloaded units, we have extensively reviewed the available literature on head and neck cancer. We confirmed a large deleterious effect of prolonged OTT on both loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 77 publications
1
57
1
3
Order By: Relevance
“…15 Longer than standard treatment duration has a negative impact on outcomes of radiotherapy for head and neck cancer, with loco-regional control loss of 1.2% per day or 12-14% per week. 30 Hypofractionated protocols are expected to cause more frequent late complications, while accelerated protocol should cause more acute toxicity, contrary to our results shown in Table 4. 13,31,32 In our study 2 out of 3 manifestations of early toxicity graded 2 or more according to the Dische scale were more frequent in the H group while 3 out of 9 late toxicity manifestations occurred more frequently in the A group.…”
Section: Discussioncontrasting
confidence: 95%
“…15 Longer than standard treatment duration has a negative impact on outcomes of radiotherapy for head and neck cancer, with loco-regional control loss of 1.2% per day or 12-14% per week. 30 Hypofractionated protocols are expected to cause more frequent late complications, while accelerated protocol should cause more acute toxicity, contrary to our results shown in Table 4. 13,31,32 In our study 2 out of 3 manifestations of early toxicity graded 2 or more according to the Dische scale were more frequent in the H group while 3 out of 9 late toxicity manifestations occurred more frequently in the A group.…”
Section: Discussioncontrasting
confidence: 95%
“…In combination, although these effects are independent of a facility change in our multivariate analysis, they suggest an area that could be addressed to potentially improve patient outcomes because several studies have demonstrated worsened disease control with prolongation of the treatment course . Estimates demonstrate that each day of delay in radiation leads to a 0.7% to 1% drop in local control . Most important is that this factor may be the most easily modifiable, in that by minimizing treatment breaks, providers at LVRFs may be able to improve outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…A number of studies shows overall treatment time (OTT) to be a critical predictor of the clinical outcome in HNC patients with the main explanation being the fast tumor cell repopulation [30,31]. Gonzalez et al reviewed sixty-five articles confirming a large deleterious effect of prolonged OTT on local control and overall survival [32]. In these studies, the authors found that the delays in RT can result in an average loss of loco-regional control (LRC), ranging from as low as 1.2% per day to as high as 12-14% per week.…”
Section: Disease Controlmentioning
confidence: 99%